COLLABORATIVE MANAGEMENT IN STUNTING PREVENTION IN MAKASSAR CITY - Nandasari, Nandasari; Sakawati, Herlina; Akib, Haedar; Fitri, Anisa (Universitas Negeri Makassar, 2025)
This study aims to identify and describe collaborative management in stunting prevention in Makassar City. This study uses a descriptive qualitative research method which will describe more deeply the focus of the problem to be studied. To achieve this goal, the researchers used data collection techniques through observation, interviews and documentation. The results of the research show that in general the collaboration between Bappeda Makassar City, Hadji Kalla Foundation, and Jenewa Institute has been running optimally. According to research results based on collaborative process theory from Ring and Van de Ven, it was found that the negotiations had gone well until an agreement was reached that benefited all parties, the commitment in the form of minutes and the MoU resulted in a collaborative program Training for Making MP-ASI Made from Local Raw Materials in order to prevent stunting, the implementation of the program was carried out well and smoothly, a thorough assessment shows that the results of the Training Program for Making MP-ASI with Local Raw Materials provide benefits to community who are participants in the program.